Bubble collisions on parallel arranged fibers. (September 2019) - Park, Ryeol; Kim, Wonjung
Highlights: Experimental and theoretical investigation of bubble collisions on parallel arranged fibers. A regime map displaying the collision outcomes classified into capturing, single bubble rising, and splitting. Scale analysis to explain the regime boundaries. The dependence of the daughter bubble size on the impact offset for splitting. Abstract: We report an experimental and theoretical investigation of bubble collisions on parallel arranged fibers. Using high speed videography, we visualized the impact outcomes and classified them into three modes: capturing, single bubble rising, and splitting. The experimental results demonstrate that the impact mode is mainly determined by the distance between the fibers as well as the rising speed of the bubble. We present the results in a regime map, displaying the dependence of the impact outcomes on dimensionless parameters: Web = ρUb 2 D / σ, Bo = ρgD 2 / σ, and d/D in the range of 0 ≤ Web ≤ 25, 0.4 ≤ Bo ≤ 0.7, 0.30 ≤ d/D ≤ 0.75, where ρ is the liquid density, Ub is the collision speed of bubble, D is the bubble diameter, σ is the surface tension, g is the gravitational acceleration, and d is the inter-fiber distance. The observed regime boundaries are explained with scale analysis. We also examined the size of daughter bubbles for splitting cases, and the results unveil the critical dependence of the daughter bubble size on the impact offset rather than on the collision speed. The results are expected to be widely used to control bubble filtration or generation in a variety of engineering systems aimed at improving heat and mass transfer using bubbles.